Oligodendrocytes Development and Wnt Signaling Pathway - Hussain Soomro Shahid; Jie Jifu; Fu Hui (International Journal of Human Anatomy, 2018)
Oligodendrocytes are specialized glial cell in central nervous system (CNS) responsible for the formation of myelin sheath around the axon. Oligodendrocyte proliferation and differentiation is regulated by Wnt signaling pathway, at various stages. However, different study groups have described controversial conclusions about the effect of Wnt on oligodendrocytes precursor cells (OPCs) development. Initially it has been proposed that Wnt pathway negatively regulates the OPCs proliferation and differentiation but recently some studies have described that Wnt promotes the differentiation of OPCs. After carefully reviewing the literature, we believe that Wnt play multiple roles in OPCs differentiation and its function is time (stage) and dose sensitive. Low to moderate activation of Wnt promotes OPC development, while too much or too low is inhibitory. Current evidences also suggested that in early developmental stages, Wnt inhibits the OPCs formation from neural progenitors and differentiation into immature oligodendrocytes. But in late stages Wnt plays promoting role in differentiation and maturation of oligodendrocytes. This review summarized the updated information regarding the critical role of Wnt signaling cascade in proliferation and differentiation of OPCs.
Keywords: Oligodendrocyte precursor cells